Guided bone grafting for atrophic mandible (Research, Society and Development, 2024)
Guided bone grafting for atrophic mandible is an advanced technique used to reconstruct and restore bone structure in mandibles that have experienced significant bone loss. This approach is particularly indicated for patients needing dental implants, whose bone structure is insufficient to support them. The procedure involves using bone graft materials placed in the affected area to stimulate new bone formation. Barrier membranes may be used to guide bone growth and prevent unwanted soft tissue invasion. Grafts can be autologous, allogenic, or synthetic, depending on the patient's specific needs and mandibular condition. This technique provides a solid and stable base for future dental implants, significantly improving the patient’s oral functionality and aesthetics. The success of the procedure relies on proper preoperative assessment, meticulous surgical planning, and stringent postoperative care to ensure effective integration of the graft with existing bone. Thus, this narrative literature review aims to analyze publications on guided bone grafting for atrophic mandible.